2016
DOI: 10.20517/2347-9264.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Current prognosis and quality of life following surgical treatment for head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers in the world with a close relation with some risk factor like, tobacco, alcohol consumption and more recently, with human papilloma virus infection. A review of the literature about actual prognosis and quality of life in HNSCC has been done analysing the results of surgical treatment and their impact on the quality of life of patients. Despite the elevated incidence of HNSCC, the survival rate has increased considerably over the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 20 , 21 Despite increased serum exosomal miR‐210 expression was previously reported in glioma and renal cancer patients 13 , 22 raising doubts on its specificity for OSCC diagnosis, our and previous findings 12 demonstrate that miR‐210 act as an oncomiR in OSCC and its expression is not affected by age, gender, or relevant pathological variables such as TNM classification, further reinforcing the concept that EV‐miR‐210 secretion is indeed strictly related to the presence of the OSCC per se . From a clinical point of view, the early detection of OSCC offers several advantages: firstly, it allows to perform a conservative organ function surgery improving the quality of life of the patient after cancer removal 23 ; secondly, the early diagnosis could identify these tumors before they spread in the lymph node or invade surrounding tissue. 24 Finally, it has been shown that the removal of OSCC in an early stage prolongs the survival rate of these patients.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Despite increased serum exosomal miR‐210 expression was previously reported in glioma and renal cancer patients 13 , 22 raising doubts on its specificity for OSCC diagnosis, our and previous findings 12 demonstrate that miR‐210 act as an oncomiR in OSCC and its expression is not affected by age, gender, or relevant pathological variables such as TNM classification, further reinforcing the concept that EV‐miR‐210 secretion is indeed strictly related to the presence of the OSCC per se . From a clinical point of view, the early detection of OSCC offers several advantages: firstly, it allows to perform a conservative organ function surgery improving the quality of life of the patient after cancer removal 23 ; secondly, the early diagnosis could identify these tumors before they spread in the lymph node or invade surrounding tissue. 24 Finally, it has been shown that the removal of OSCC in an early stage prolongs the survival rate of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, in the literature it is reported that up to 20% of patients will have a final diagnosis of positive or close margins despite having negative FS intraoperatively. Because of the difficulties in treating this challenging form of cancer, the estimated five-year survival rate of SCC is only 40 to 60% with treatment [131]. There exists a great need to provide more near-real-time information and guidance to the operating surgeon.…”
Section: Medical Hyperspectral Imaging For Cancer Analysismentioning
confidence: 99%
“…In the United States, 50 000 cases are diagnosed each year and more than 10 000 deaths are attributable to this disease 1 . The survival rate of HNSCC is only 50% by 5 years after diagnosis, and this has improved little in the past 30 years despite significant progress in therapeutic interventions, including surgery, radiotherapy, and chemotherapy 2,3 . A better understanding of the underlying molecular mechanisms that regulate HNSCC progression will help identify new prognostic biomarkers for prediction of patients' survival rate and may also indicate novel therapeutic targets to improve treatment response in patients with HNSCC.…”
Section: Introductionmentioning
confidence: 99%